Managing Windows 2000 network services - Syngress Media, Inc. ([U.S.] : Syngress Media ; London : International Thomson, 2000)
Many organizations and network administrators are looking for information on Windows 2000 and its new features. IT professionals responsible for installing, configuring and managing Microsoft products will be highly motivated to migrate to this new technology, based on its promise of reducing administrative overhead. Microsoft Windows 2000 Server (the predecessor to Windows NT 4 Server) integrates network services for companies and administrators to set up and manage networks, remote access and extranets, as well as to manage other communications. Managing Windows 2000 Network Services will be the first book to focus exclusively on networking and integrated voice, video, and data on networks. Readers will learn how to deploy and integrate all Windows 2000 networking technologies within an enterprise network. * The publication of the book will be with or soon after the release of Windows 2000 * Focuses completely on Network Services.
Keywords: Microsoft Windows (Computer file).; Operating systems (Computers).; Microsoft Windows 2000 (Computer file); Electronic books